TO STUDY THE AWARENESS AND KNOWLEDGE OF CUSTOMERS FOR ORGANIC FOOD PRODUCTS - Shukla, Anurag; Khare, Amit (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The rising awareness of health and environmental sustainability has significantly contributed to the growing demand for organic food products. However, the level of consumer awareness and knowledge regarding these products varies widely. This study aims to assess the key factors influencing consumer awareness and understanding of organic food, including their perception of benefits, certifications, and distinctions from conventional food. A structured survey was conducted with a sample size of 107 respondents to gather insights into consumer familiarity with organic labeling, purchasing motivations, and common misconceptions. The findings highlight the impact of critical factors such as health consciousness, environmental concerns, trust in certification authorities, marketing strategies, and socio-economic influences on consumer decisions. Additionally, the study examines the role of education, media exposure, and brand credibility in shaping consumer knowledge. The results provide valuable insights for businesses, policymakers, and marketers to enhance consumer education and develop effective strategies for promoting organic food products. The study concludes with recommendations to bridge knowledge gaps and encourage informed purchasing decisions, ultimately fostering a healthier and more sustainable future.